2008
DOI: 10.1016/j.yexcr.2007.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the osteogenic effects of laminin-332 utilizing specific LG domains: LG3 induces osteogenic differentiation, but not mineralization

Abstract: The overall mechanisms governing the role of laminins during osteogenic differentiation of human mesenchymal stem cells (hMSC) are poorly understood. We previously reported that laminin-332 induces an osteogenic phenotype in hMSC and does so through a focal adhesion kinase (FAK) and extracellular signal-related kinase (ERK) dependent pathway. We hypothesized that this is a result of integrin-ECM binding, and that it occurs via the known alpha3 LG3 integrin binding domain of laminin-332. To test this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…neurogenic has been suggested by others (67) and osteogenic differentiation (20). Furthermore, previous studies have also indicated that activation of a focal adhesion kinase (FAK) and extracellular signal-related kinase (ERK) dependent pathway by laminin binding to LG3 integrin binding domain mediated osteogenic differentiation but did not increase matrix mineralization, demonstrating that the activation of FAK and ERK signaling is not sufficient to induce complete osteogenic differentiation in vitro (68). A previous study indicated that phytoestrogen, puerarin, act via phosphatidylinositol-3-kinase/Akt (PI3K/Akt) (54) thus complete osteogenic differentiation might need more than one signaling pathway working in concert with each other.…”
Section: Discussionmentioning
confidence: 89%
“…neurogenic has been suggested by others (67) and osteogenic differentiation (20). Furthermore, previous studies have also indicated that activation of a focal adhesion kinase (FAK) and extracellular signal-related kinase (ERK) dependent pathway by laminin binding to LG3 integrin binding domain mediated osteogenic differentiation but did not increase matrix mineralization, demonstrating that the activation of FAK and ERK signaling is not sufficient to induce complete osteogenic differentiation in vitro (68). A previous study indicated that phytoestrogen, puerarin, act via phosphatidylinositol-3-kinase/Akt (PI3K/Akt) (54) thus complete osteogenic differentiation might need more than one signaling pathway working in concert with each other.…”
Section: Discussionmentioning
confidence: 89%
“…Laminin-332 is also detected in periosteum, not only in the basement membrane [21]. Moreover, laminin-332 affects osteoblast differentiation and calcification [22] [23] [24]. Therefore, laminin-332 plays important roles not only in epithelial cell function but also in the function of mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several ECM-proteins, such as type I collagen, laminin-5, and vitronectin, have been identified as regulators of MSC-adhesion and inducers of osteogenic differentiation in vitro . 410 Fetal calf serum (FCS) is widely used for cell culture, 47 but in the context of possible further clinical applications animal serum does not meet the European Good Manufacturing Practice (GMP) regulations for medical products. The risk of immunological reactions, prion transmission and potential metabolic changes in cultured cells must be considered.…”
Section: Introductionmentioning
confidence: 99%